Influence of Use Lactobacillus fermentum L23 and Streptococcus thermophilus with Dragon Fruit Extract (Hylocereus Polyrhisuz) to Quality of Microbiology, Chemistry and Organoleptic Value of Yoghurt - Purwati, Endang; Rezzy Pratama, Dhiva; Melia, Sri; Purwanto, Hendri (International Journal of Engineering and Technology, 2019)
The difference between starter concentration and dragon fruit (Hylocereus polyrhizus) extract concentration on the quality of microbiology, Chemistry, and organoleptic value of yoghurt. The method of research was the experimental method by using a Randomized Block Design (RBD) 3x4 factorial pattern with 2 replicates as a group. Factor A starter concentration that is A1: 4%, A2: 5%, A3: 6% and Factor is dragon fruit extract that is B1: 0%, B2: 1%, B3: 2%, B4: 3% . The parameters measured were Total Lactic Acid Bacteria colonies, Water content, protein content, fat content, antioxidant activity, pH Value and organoleptic value of yoghurt. The results show that there was a real interaction (P <0.05) concentration of the starter (factor A) and concentration of the extract dragon fruit (factor B) against total lactic acid bacteria colonies. but there was no significant interaction (P> 0.05) on water content, protein content, fat content, antioxidant activity, pH value and organoleptic value of yoghurt. factor A can give a real effect (P <0.05) to antioxidant activity and pH value of yoghurt. While factor B can give a very real effect (P <0.01) on water content, protein content, fat content, antioxidant activity and pH value of yoghurt. Then for organoleptic value there is no significant effect (P> 0.05) from each factor to organoleptic value of yoghurt. The best percentage addition for yoghurt was 5% at starter concentration and 2% at dragon fruit (Hylocereus polyrhizus) extract concentration with total lactic acid bacteria colonies 170 Ã— 108 CFU/ml, water content 81.22%, protein content 4.65%, fat content 3.58%, antioxidant activity 44.53%, pH value 4.4 and organoleptic value still in range preferred by panelists.Â Â